Conductometric Study of the Solution Mixtures of Urinary Stone Forming Anions, Urine and Citric Acid - Rao, T.V.R.K.; Bano, Sofia (Asian Journal of Chemistry, 2010)
Measurement of electrical conductance of the mixtures of solutions of urinary stone forming anions, viz., oxalate or phosphate and stone inhibitor, viz., citric acid have been carried out in different proportions in the presence and absence of urine as mixture component. Diagnosis and inhibition of urolithiasis has been discussed in the light of conductance data.